Resistance prior to aerobic training intra-session sequence optimizes strength and hypertrophy gains in water-based exercise - Cadore, E.; Pinto, S. S.; Alberton, C. L.; Zaffari, P.; Bagatini, N. C.; Radaelli, R.; Pinto, R. S.; Kanitz, A. C.; Bottaro, M.; Colado, J. C. S.; Kruel, L. F. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
To the best of our knowledge, there is no study regarding the effect of exercise order manipulation during concurrent training in the water-based exercises on the neuromuscular and cardiorespiratory adaptations in young women. Therefore, the aim of the study was to compare the effects of different intra-session exercise orders in the neuromuscular and cardiorespiratory adaptations induced by concurrent water-based exercise training in young women. Methods: Twenty-six healthy young women (25.12±2.94years) were randomly placed into two concurrent training groups: resistance training prior to (RA, n=13) or after (AR, n=13) aerobic training. Subjects trained resistance and aerobic training in water environment 2 times per week performing both exercise types in the same training session. The peak oxygen uptake (VO2peak), oxygen uptake corresponding to the first and second ventilatory thresholds (VO2VT1 and VO2VT2) was evaluated during a maximal incremental test on a treadmill before and after the training. Moreover, maximal dynamic strength (one repetition maximum test) of the knee extensors and elbow flexors were evaluated and the quadriceps femoris muscle thickness was determined by ultrasonography.